Analisis Passing dan Shooting Tim Futsal Putri Venus Bintang Manis Angels pada Pertandingan Liga Nusantara Jawa Tengah Tahun 2021 - Ratri, Novitasari Mulat; Yuwono, Cahyo (Universitas Negeri Semarang, 2023)
This is what makes researchers want to know how big theabilities are passing and shooting in the Central Java Nusantara League match in 2021.. The research method used is quantitative research with a descriptive analysis approach. The population in this study was the Venus Bintang Manis Angels team player, the sample in this study was to document a 2x20 minute match video. Observation instrument using Video Recording and Scooring Sheet. The data analysis used in this research is descriptive statistical analysis. Prerequisite test is done with normality test and homogeneity test. The conclusion in this research is the success rate of passing correctis very high reaching 741 times (78.2%). The accuracy level oftechnique shooting reached 67 times on target (45.0%). Research suggestions are: With the level of accuracy and effectiveness of basictechniques passing and shooting a team will be able to dominate the match and create more goals